Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.neuropharm.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and molecular interaction studies of a highly stable, tarantula peptide modulator of acid-sensing ion channel 1

Abstract: Please cite this article as: Er, S.Y., Cristofori-Armstrong, B., Escoubas, P., Rash, L.D., Discovery and molecular interaction studies of a highly stable, tarantula peptide modulator of acid-sensing ion channel 1, Neuropharmacology (2017), doi: 10.1016/j.neuropharm.2017.03.020. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
(91 reference statements)
3
21
0
Order By: Relevance
“…Testing of these mutants for sensitivity to PcTx1 identified Arg175 and Glu177 (Cys and Gly in ASIC1b, respectively) to play a key role in the subtype dependent effects of Hm3a. Er et al also showed that Hm3a potentiates acid-induced currents in oocytes co-injected with rASIC1a and rASIC1b (Er et al, 2017), an effect we observed for PcTx1 (unpublished observations), which has not previously been noted.…”
Section: Hm3asupporting
confidence: 76%
See 1 more Smart Citation
“…Testing of these mutants for sensitivity to PcTx1 identified Arg175 and Glu177 (Cys and Gly in ASIC1b, respectively) to play a key role in the subtype dependent effects of Hm3a. Er et al also showed that Hm3a potentiates acid-induced currents in oocytes co-injected with rASIC1a and rASIC1b (Er et al, 2017), an effect we observed for PcTx1 (unpublished observations), which has not previously been noted.…”
Section: Hm3asupporting
confidence: 76%
“…However, it remained unstudied and unreported until now. In this issue of Neuropharmacology we present the characterisation of π-TRTX-Hm3a (Hm3a) isolated from the Togo starburst tarantula (Heteroscodra maculata) (Er et al, 2017). Hm3a has five amino acid substitutions compared to PcTx1 and is shorter by three residues at the C-terminus (Figure 2A).…”
Section: Hm3amentioning
confidence: 99%
“…Despite its high sequence similarity with PcTx1, Hm3a showed higher levels of stability over 48 hr. Overall, Hm3a represents a potent, highly stable tool for long term in vitro and in vivo experiments (Er, Cristofori-Armstrong, Escoubas, & Rash, 2017).…”
Section: Polypeptide Modulatorsmentioning
confidence: 99%
“…These oxins have been ins rumen al o s udy he s ruc ure, properties, functional expression in above-mentioned physiopa hological s a es. Hcr1b-1 and Hm3a bo h are peptide oxins similar o PcrTx1 are ob ained from spider, snake and sea anemone venoms argeting for ASICs [59][60]. Dendro oxins (DTx) are a group of peptide oxins purified from he venom of several mamba snakes and α-DTx selectivi y and i s po ential in eraction wi h ASICs should be aken in consideration for inhibiting ASICs induced curren [61].…”
Section: Pharmacological Agents Availablementioning
confidence: 99%